Étude du développement de l’agglomération lyonnaise depuis 1950 - Nicolas Ferrand (Projets de Paysage)
The study of the urbanization of the Lyon area is based on identifying and mobilization of large numbers of archives and heterogeneous sources. One of the challenges for the establishment of a new tool for analysis the urban sprawl is based on integration of these data into a coherent whole, with a Geographical Information System (GIS). This new tool allows tracking per hectare, the development of urbanization, based on its morphological characteristics since 1950. The aim is to track urban sprawl but also the renewal of the city to itself. The latest developments of this tool have been made in collaboration with the Lyon area urbanism agency.